An Overlay Architecture for Achieving Total Flexibility in Internet Communications - Cassagnes, Cyril; Bromberg, David; Magoni, Damien (Realizacja globalnej elastyczności komunikacji internetowej poprzez architekturę nakładkową, 2010)
The current state of the art for Internet communications shows that they are not flexible enough considering the capabilities of the current equipments. The mobile equipments are still unable to transfer a communication from one device to another without interrupting the communication. In the same way, although we have the choice of many applications, it is still impossible to transfer a communication from one application to another in a given device without interrupting the communication. Only device mobility is currently ensured and in a very limited way. We have a wide access to layer 2 mobility with technologies such as WiFi, WiMax and 3 + G. We also have some limited access to layer 3 mobility with the Mobile IP architecture. This paper presents a new architecture designed to bring total flexibility to Internet communications.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 147, s. 39-50
Keywords: architecture; flexibility; overlay network